Child Exploitation Reflected In Charles Dickens'oliver Twist Novel (1838): A Sociological Approach - Estiyana, Aulia, Titis Setyabudi, S.S.M.Hum (2016)
This study is proposed to analize how child exploitation reflected in Oliver Twist (1838) by Charles Dickens. The objectives of this study are to analyze cause and effect of child exploitation according to the Oliver Twist (1838) novel by Charles Dickens'. The writer employs qualitative research. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then the secondary data are taken from other sources which are related to the primary data such as the literary books, dictionary, some articles related to the novel and website about Oliver Twist novel. The technique of data collection is library research. The technique of analyzing data is descriptive qualitative. Based on sociological analysis, the writer is find five aspects such as social aspect, economic aspect, cultural aspect, religious aspect, and science and technology aspect based on Oliver Twist novel by Charles Dickens'. The cause and effect reflects in Oliver Twist novel (1838)by Charles Dickens'.